Diamond coated artificial cardiovascular devices - Zeng, Hongjun (Surf Coat Technol, 2016)
Ultrananocrystalline diamond (UNCD), an extremely smooth, low cost diamond coating was successfully developed herein for antithrombogenic application which requires high biocompatibility, low wear, low friction, and chemical inertness. The substrate materials utilized in the Jarvik 2000 ventricular assist device (VAD), silicon carbide and titanium alloy, provide an excellent substrate match for UNCD integration. The paper addresses the development of medical-quality UNCD films to significantly improve the knowledge base regarding the defect mechanisms of UNCD films, to reduce or eliminate known wear-inducing imperfections in the film, and to thoroughly characterize and test the films as well as assembled UNCD-coated VADs. After the defect reduction and seeding experiments to improve film adhesion and coating quality, the best candidate deposition method has been down-selected for coating and assembly of VAD parts from Jarvik Heart. The coated and assembled devices have been tested with mechanical and blood-simulating fluid hydrodynamic testing at Jarvik Heart for full verification of the new coating technology. UNCD interface takes advantage of combining unmatched durability and antithrombogenicity.